Association between subjective well-being trajectories and anxiety/depression: findings from a nationally representative cohort study - Wang, Xinyu; Ke, Qing; Leng, Pengqun; Liu, Dan; Zeng, Wen (Frontiers in Psychology, 2025)
BackgroundSubjective well-being (SWB) in older adults is a key indicator of psychological health and quality of life. However, research on trajectories of SWB is quite limited, and little is known about the relationship between anxiety/depression and trajectories of SWB in older adults. This study aimed to identify the trajectories of SWB in older adults and examine the association between anxiety/depression and trajectories of SWB.MethodsA population-based cohort study, the National Health and Aging Trends Study in the United States from 2015 to 2022. SWB was assessed through 11 items, including positive/negative emotions (4 items), self-realization (4 items), self-efficacy, and resilience (3 items). Anxiety/depression symptoms were assessed by the Patient Health Questionnaire-4 (PHQ-4). The group-based trajectory modeling identified trajectories. The design-based weighted multinomial logistic regression was used to examine the association between anxiety/depression and SWB trajectories.ResultsOf 5,057 included older adults, 59.22% were aged between 60 and 74 years old, 55.5% were female, and 82.23% were non-Hispanic White. Four trajectories of SWB were identified: Group 1 (low, slightly-declining SWB, 8.7%), Group 2 (moderate, declining SWB, 25.4%), Group 3 (moderate, slightly-declining SWB, 42.2%), and Group 4 (high, slightly-declining SWB, 23.7%). Higher anxiety/depression scores were associated with low or moderate SWB trajectories: Group 1 (odds ratio, OR: 3.35, 95% confidence interval, CI: 2.73, 4.00), Group 2 (OR: 2.59, 95% CI: 2.20, 3.00), and Group 3 (OR: 1.80, 95% CI: 1.49, 2.18).ConclusionThe trajectories of SWB varied among older adults. Anxiety/depression was significantly associated with SWB trajectories. Evidence-based effective strategies for the management of anxiety/depression are needed to maintain SWB at a high level in older adults.What does this paper contribute to the broader global clinical community?•This study identifies four distinct trajectories of subjective well-being in older adults.•Anxiety/depression is significantly associated with subjective well-being trajectories.•Our study highlights the importance of screening and longitudinally tracking SWB in older adults.•Effective prevention and intervention of anxiety/depression is a high priority to maintain or improve SWB in older adults.